A study on perceived ease of use and knowledge of farmers in Kada, Kelantan towards herbicide application on paddy farming / Nurhidayah Mohd Nawi - Mohd Nawi, Nurhidayah (Faculty of Plantation and Agrotechnology, 2015)
Oryza sativa L. or paddy from family Poaceae is one crop in Malaysia become an important staple food in the daily lives of their people. According to the Statistics Unit, (2012), the total population increased from 27.90 million in 2009 to 28.25 million in 2010. The rapid incremental of population have influence the demand for paddy increased. It has become a challenge for us to meet that demand by producing the high yield of paddy. However, but there are several constraint that prevent from achieving high rice yield, among these are the problem of weeds in paddy fields. Weeds are the unwanted plant that competes with our crop in term of light, nutrient and also space which is directly affect the yield production of paddy (Hamid, 2012). Weeds control is really needed to all types of paddy cultivation whether it is upland rice or lowland rice in order to increase the paddy production. But nowadays, due to the increase of weeds population, labour in shortage supply and to increase the level of efficiency in weeds control, farmers are more recommended to use the chemical control by using herbicide as an alternative way to control the weeds beside it is more efficient and economical. It is because herbicides are very effective and take a short time work (Kosina.P, 2007). Herbicide application is the most practical and efficient way in inhibit the weed competition and reducing the losses of paddy production. However, in order to achieve that mission, it is important to know whether the farmers' perceived ease of use and knowledge are really affecting the herbicide practice in their paddy fields. By knowing that, is hoped the farmers can reduce the weed population and also can increase their paddy production in efficient way. The purpose of this study is to determine whether there is relationship between perceived ease of use and knowledge of farmers towards herbicide application to control weed infestations in their paddy fields. Based on the use of questionnaires that will conducted in the study area which is Pertubuhan Peladang Kawasan Bukit Jawa (PPK Bukit Jawa), about 120 of paddy farmers' perceived ease of use and knowledge towards herbicide application will investigated. The quantitative data will analysed by Multiple regression analysis. At the end of this study, result revealed that the perceived ease of use and knowledge level of farmers give significant effect to them to apply herbicide in their paddy field. But, the factor that more influences them is perceived ease of use related to herbicide application in weed population control. It is recommended to find out the perceived ease of use and knowledge level of paddy farmers that operate the large scale of paddy plantation, purposely to obtain more perceived ease of use or any brilliant idea that can improve the weed management and surely can increase the yield production of paddy.